2014
DOI: 10.2527/jas.2014-7754
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of zilpaterol hydrochloride and ractopamine hydrochloride on live performance and carcass characteristics of calf-fed Holstein steers12

Abstract: Holstein steers (n = 2,275) were assigned to 1 of 3 treatments: 1) a control diet containing no β-agonists, 2) a diet that contained zilpaterol hydrochloride (ZH; 8.3 mg/kg [100% DM basis]) for 20 d with a 3-d withdrawal period before harvest, and 3) a diet that contained ractopamine hydrochloride (RH; 30.1 mg/kg [100% DM basis]) for 28 d before harvest. No differences (P ≥ 0.18) were detected between treatments for initial BW, BW at d 28, or DMI. Final BW, BW gain for the last 28 d, total BW gain, ADG for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
4
3
0
Order By: Relevance
“…Similar β receptor populations were found in human muscle biopsies [40, 41]. The present findings also help explain greater muscle growth efficiency in food animals supplemented with dietary β2 agonist compared to β1 agonist [4244]. …”
Section: Discussionsupporting
confidence: 79%
“…Similar β receptor populations were found in human muscle biopsies [40, 41]. The present findings also help explain greater muscle growth efficiency in food animals supplemented with dietary β2 agonist compared to β1 agonist [4244]. …”
Section: Discussionsupporting
confidence: 79%
“…Ractopamine hydrochloride has been well established for its impact on HCW; studies have shown consistent improvements when fed at 200 to 300 mg/ (animal • d). Scramlin et al (2010) reported HCW that were 5.3 kg greater in steers supplemented with 200 mg/ (animal • d) compared to controls, and similar improvements were reported by Brown et al (2014), who realized an 8.2-kg increase in steers fed 300 mg/(animal • d).…”
Section: Discussionsupporting
confidence: 63%
“…In spite of the muddy conditions, animal performance data from the present experiment are consistent with results from previous experiments ( Bass et al, 2009 ; Vogel et al, 2009 ; Brown et al, 2014 ) when RH was fed to Holstein steers during the final 28 to 38 d of the feeding period. Previous studies have reported greater BW gain (4.3 to 8.0 kg), increased ADG (0.05 to 0.28 kg/d), and an improvement in G:F (14.2% to 16.6%) in calf-fed or yearling Holstein steers fed 200 to 300 mg·steer −1 ·d −1 of RH compared with steers not fed RH ( Bass et al, 2009 ; Vogel et al, 2009 ; Brown et al, 2014 ). In the present experiment, BW was improved by 6.3 and 7.2 kg, ADG by 0.20 and 0.22 kg/d, and G:F was increased 20.8% and 21.7%, when steers were fed 300 and 400 mg·steer −1 ·d −1 of RH, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Previous research has shown the addition of RH to the diet of beef or Holstein steers prior to harvest resulted in improvement in average daily gain (ADG), gain-to-feed ratio (G:F), hot carcass weight (HCW), and carcass leanness ( Arp et al, 2014 ; Brown et al, 2014 ; Bittner et al, 2017 ). However, research determining the effects of feeding RH at varying doses and durations in Holstein steers is limited.…”
Section: Introductionmentioning
confidence: 99%